John Walkenbach's favorite Excel 2010 tips & tricks - Walkenbach, John (Mr. Spreadsheet's bookshelf., 2010)
Presents a collection of shortcuts and workarounds for Microsoft Excel 2010, covering such topics as creating charts, using formulas, running macros, and creating custom add-ins.